ANALYSIS OF TOTAL COSTS OF BREAST CANCER CEMOTHERAPY PATIENTS BASED ON USE OF CHEMOTHERAPY REGIMEN ON JKN PATIENTS IN SANGLAH RSUP - Wintariani, Ni Putu; Okadwicandra, Ni Made; Jaelani, Abdul Khodir (Jurnal Endurance, 2017)
Breast cancer is the first sequence of most attacking women in Indonesia. The high cost of care and old services is a major problem in the prevention of breast cancer. This study aims to determine the relationship between the total cost of the Sanglah Denpasar hospital with the chemotherapy regimen of breast cancer of JKN patients at Sanglah Hospital Denpasar. Test homogeneity using Levene test method. Test normality using Kolmogorov-Smirnov. One way ANOVA test results showed a significant relationship between chemotherapy therapy regimen (FAC, FAC + PAXUS, FEC, AC, AC + PAXUS) with total real cost in breast cancer chemotherapy patients (p = 0.001). The total rill cost was greater in the group receiving FAC + PAXUS, FEC, and AC + PAXUS regimens than the group receiving FAC and AC therapy regimens. This can be caused by a large pharmaceutical cost component in the FAC + PAXUS, FEC, and AC + PAXUS groups. Pharmaceutical costs account for 76.84-85.80% of the total real cost of breast cancer patients receiving chemotherapy. More drug combination factors can lead to higher total rill costs in patients receiving FAC + PAXUS, FEC, and AC + PAXUS.